PERAN PERBANKAN SYARIAH DALAM MENDORONG AGRO INVESTASI - Yulizar D. Sanrego; Aam S. Rusydiana (Jurnal Keuangan dan Perbankan, 2009)
Indonesia is an agrarian country. More of 40 percent of citizens are in theresector. However, it is not easy to face the challenges in agriculture. One of primary problemin agriculture sector is about capital endorsement. This paper tries to analyze the chanceof financing agriculture sector may be given by Islamic banking industries in Indonesia, thechallenges and steps that will be done, using descriptive statistic. The results show that shariafinancing scheme has potentially very powerful prospect as an alternative within agriculturesector problems in Indonesia. To motivate the implementation, we hope that sharia bankingindustries braver and more incessant give the financing by existing various scheme. Forrecommendation, Bank Indonesia as monetary authority could offer full support by givingincentives they need.